PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (Studi Pada CV. Kezia Cipta Gemilang) - Friscila Putri Nurida, 14.05.51.0077; Murdiyanto, Agus (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the influence of work environment ,conpensation , and style of leadership on the employees performance of CV. Kezia Cipta Gemilang. Respondents research it consists of 82 on officials of CV. Kezia Cipta Gemilang. Model analysis the data used was test validity with product moment, reliability testing with Cronbach Alpha and multiple linear regression as using software IBM SPSS version 20,0to examine and prove a hypothesis research. The data collected following the completion of testing the results all data expressed valid and reliable. The result of analysis and discussion shows that: (1). Work environmentIt has some positive effects and significant impact on the employees performance, (2). conpensation have had a positive effect and significant of the performance of employees, and (3).style of leadership have had a positive effect and insignificant of the performance of employees. Simultaneously work environment ,conpensation , and style of leadership on the employees performance Keyword : Work environment, conpensation, style of leadership, Employees performance